Artificial Neural Networks for Dairy Industry: A Review - Goyal, Sumit (Journal of Advanced Computer Science & Technology, 2012)
Artificial Neural Networks (ANNs) have been implemented in almost every field, viz., science, technology, medicine and engineering as they have proved useful tools for obtaining the desired output including the analyses and shelf life prediction in case of food products. This review discusses the systematic information available in the literature concerning the implementation of ANN models for shelf life determination of milk, various dairy products, viz., yoghurt, chocolate, butter, cheese, kalakand, dairy confections and milk based coffee drinks, which would be very useful for dairy industry, consumers, wholesalers, retailers, regulatory agencies, food researchers and academicians.